2019
DOI: 10.1371/journal.pone.0210760
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium affects body composition and lipid metabolism in rats

Abstract: Calcium (Ca) intakes may affect cardiovascular disease risk by altering body composition (body weight and fat) and serum lipid profile, but results have been inconsistent and the underlying mechanisms are not well understood. The effects of dietary Ca on body composition and lipid metabolism were examined in rats. Male Sprague-Dawley rats were fed high-fat, high-energy diets containing (g/kg) low (0.75Ca, 0.86 ± 0.05; 2Ca, 2.26 ± 0.02), normal (5Ca, 5.55 ± 0.08) or high (10Ca, 11.03 ± 0.17; 20Ca, 21.79 ± 0.15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 70 publications
0
22
0
1
Order By: Relevance
“…It seems that high intake of calcium in present study may possibly be associated with reduced risk of overweight and obesity. Apparently, the mechanism of this effect is related to the reduction of PTH and 1, 25-Dihydroxyvitamin D which leads to inhibition of lipogenesis and increase lipolysis and ultimately increase in fecal fat excretion due to the formation of soaps (45). Perhaps this is a reason for the negative relationship seen in this study.…”
Section: Discussionmentioning
confidence: 68%
“…It seems that high intake of calcium in present study may possibly be associated with reduced risk of overweight and obesity. Apparently, the mechanism of this effect is related to the reduction of PTH and 1, 25-Dihydroxyvitamin D which leads to inhibition of lipogenesis and increase lipolysis and ultimately increase in fecal fat excretion due to the formation of soaps (45). Perhaps this is a reason for the negative relationship seen in this study.…”
Section: Discussionmentioning
confidence: 68%
“…They explained that the low level of free fatty acid (FFA) and glycerol due to reduced lipolytic activity leads to stable serum TG levels in response to a low and very low calcium diet (He et al, 2011). Alomaim et al (2019), observed that a high calcium diet (20 Ca) having calcium concentration (20.1 ± 0.1 g Ca/ kg wet weight) lowered the serum TC and LDL-C level in comparison to rats fed with normal (5Ca) having calcium concentration (5.08 ± 0.07 g Ca/kg wet weight) or low calcium diets (0.75 Ca or 2 Ca) having concentration (0.789 ± 0.048 or 2.09 ± 0.01 g Ca/ kg wet weight) after 10 weeks of the experimental period. This improvement in the lipid profile was achieved by inhibiting the bile acid reabsorption and suppressed the absorption of neutral sterols as well as saturated and trans fatty acids in response to a high calcium diet.…”
Section: Effec T Of D Ie Tary C Alci Um On Hypertens Ionmentioning
confidence: 99%
“…13 On the other hand, it can also exert coordinated regulatory effects on the adipocyte lipid metabolism and triacylglycerol storage by increasing the gene expressions on the lipogenic and de novo lipogenesis and inhibiting the lipolysis and thermogenesis to result in excessive lipid accumulation in the hepatic tissueand associated NAFLD. 14,15 Recently, emerging evidence has shown that the first 1,000 d in life is a critical period for the colonization of intestinal flora and prevention of many chronic non-communicable diseases (NCD) such as NAFLD. 16 Thus, keeping adequate calcium intake in this period of the life is of a great importance for a positive calcium balance, good bone density necessary for the skeletal consolidation, and reducing the occurrence of NCD in the later.…”
Section: Introductionmentioning
confidence: 99%